Docking, characterization and investigation of β-cyclodextrin complexed with farnesol, an acyclic sesquiterpene alcohol, produces orofacial antinociceptive profile in experimental protocols. (November 2017) - Silva, Juliane Cabral; de Moraes Alcantara, Lidianne Fábia; Dias Soares, Juliana Mikaelly; e Silva, Mariana Gama; de Lavor, Érica Martins; Andrade, Valléria Matos; dos Passos Menezes, Paula; de Souza Araújo, Adriano Antunes; Leite, Laura Hévila Inocêncio; de Menezes, Irwin Rose Alencar; Scotti, Luciana; Scotti, Marcus T.; et al.
Graphical abstract: Highlights: β-cyclodextrin was used to obtain an inclusion complex with farnesol. The slurry complexation method exhibited a better complexation profile. Farnesol and βCD/FAR have an effect of reducing orofacial pain. Possible mechanisms of action farnesol are mediated by K + ATP channels and 5-HT3 receptors. Abstract: In this study, an inclusion complex with β-cyclodextrin and farnesol (βCD/FAR) was used to improve the physico-chemical and pharmacological properties of farnesol. The samples were obtained using the physical mixture, paste and slurry complexation methods and characterized by variety of methods. To evaluate the pharmacological effect, an animal model of orofacial pain induced by formalin, glutamate and capsaicin was used, and its possible mechanisms of action were evaluated. The slurry complexation method was produced with a formation energy of 3.45 kcal/mol and exhibited a better complexation profile as it presented smaller, deformed crystals compared to the other methods, with a stable complex formed. The formation energy was 3.45 kcal/mol. In the orofacial pain test induced by formalin, capsaicin and glutamate the results show that farnesol and its complex at doses of 50 and 100 mg/kg significantly decreased (p < 0.001) face-rubbing behavior. In the investigation of the mechanism of action, the administration of glibenclamide and ondansetron modified the antinociceptive effect of the farnesol, suggesting the possible participation of the ATP-sensitive K + channel (K + ATP ) and 5-hydroxytryptamine (5-HT3 ) channels/receptors. A rota-rod test did not show any significant alterations in motor performance in the groups treated with farnesol and its complex. In conclusion, farnesol and βCD/FAR reduced orofacial pain, possibly mediated by K + ATP channels and 5-HT3 receptors.